Responding to Shocks and Maintaining Stability in the West African Economic and Monetary Union - Kolerus, Christina (Departmental Papers; Departmental Paper ;, 2013)
The West African Economic and Monetary Union (WAEMU), like other monetary unions, faces a number of challenges in dealing with macroeconomic shocks. The region experiences a large number of exogenous shocks: climate-related (e.g., droughts, floods), with a heavy toll on populations and agriculture, but also economic (e.g., terms of trade), with a large impact on key sectors and the cost of living. More generally business cycle synchronization within the WAEMU seems low. Addressing these shocks, while preserving the stability of the union, is therefore a critical issue in the WAEMU.This paper discusses these issues and suggests possible reforms.